2017
DOI: 10.1016/j.ejmech.2016.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, evaluation, and CoMFA study of fluoroquinophenoxazine derivatives as bacterial topoisomerase IA inhibitors

Abstract: New antibacterial agents with novel target and mechanism of action are urgently needed to combat problematic bacterial infections and mounting antibiotic resistances. Topoisomerase IA represents an attractive and underexplored antibacterial target, as such, there is a growing interest in developing selective and potent topoisomerase I inhibitors for antibacterial therapy. Based on our initial biological screening, fluoroquinophenoxazine 1 was discovered as a low micromolar inhibitor against E. coli topoisomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
(33 reference statements)
1
18
0
2
Order By: Relevance
“…In previous studies, the FP-11g compound has been proposed as an antimycobacterial agent active against M. tuberculosis (MIC = 2.5 μM) [11]. Here we demonstrate its activity against the pathogenic NTM M. abscessus.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In previous studies, the FP-11g compound has been proposed as an antimycobacterial agent active against M. tuberculosis (MIC = 2.5 μM) [11]. Here we demonstrate its activity against the pathogenic NTM M. abscessus.…”
Section: Discussionsupporting
confidence: 63%
“…FP-11g (Scheme 1) was synthesized using our previously reported procedure [11]. The structure was confirmed by 1 H NMR, and high-resolution mass spectrometry (HRMS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difluoroquinolone derivative NSC648059 bearing a six‐membered ring linked N‐1 and C‐8 positions was found with low micromolar inhibitory activity (IC 50 : 0.8–2.0 μM) against E . coli topoisomerase I by Yu et al . Further modification indicated that the substituents at both N‐1 phenyl group and C‐7 position significantly influenced the activity and the SAR outlined in Figure .…”
Section: Structure–activity Relationshipmentioning
confidence: 99%
“…coli topoisomerase I by Yu et al . Further modification indicated that the substituents at both N‐1 phenyl group and C‐7 position significantly influenced the activity and the SAR outlined in Figure . For the N‐1 phenyl groups, 4‐NH 2 was most favorable against both E .…”
Section: Structure–activity Relationshipmentioning
confidence: 99%